2015
DOI: 10.1007/s12028-015-0220-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Red Blood Cell Transfusion on Long-Term Disability of Patients with Traumatic Brain Injury

Abstract: Our results strongly suggest an independent association between RBCT and unfavorable long-term functional outcomes of patients with TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…[1][2][3] Although anemia is associated with secondary brain injury, 4 its independent association with unfavourable outcomes is uncertain. [5][6][7] While RBC transfusion and the adoption of a more liberal transfusion strategy have been suggested to improve tissue oxygenation in the injured brain, [8][9][10][11] several observational studies report deleterious effects of transfusion in this population. 5,[12][13][14] Large clinical trials have shown that restrictive transfusion strategies (higher threshold to transfuse) are as safe as liberal strategies (lower threshold) in critically ill pediatric and adult patients.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Although anemia is associated with secondary brain injury, 4 its independent association with unfavourable outcomes is uncertain. [5][6][7] While RBC transfusion and the adoption of a more liberal transfusion strategy have been suggested to improve tissue oxygenation in the injured brain, [8][9][10][11] several observational studies report deleterious effects of transfusion in this population. 5,[12][13][14] Large clinical trials have shown that restrictive transfusion strategies (higher threshold to transfuse) are as safe as liberal strategies (lower threshold) in critically ill pediatric and adult patients.…”
Section: Résumémentioning
confidence: 99%
“…17 Of note, patients with TBI were underrepresented in these studies. 18 While uncontrolled observational studies have reported an association between transfusion or transfusion volume and adverse neurological outcome in patients with TBI, 5,9,12,13,19,20 few comparative studies have been conducted to clarify the effect of transfusion or anemia in this patient population, 21 and very few have assessed the impact of transfusion on clinical outcome. In a trial of 200 TBI patients randomized to a restrictive or liberal RBC transfusion strategy, no difference in neurologic outcome was observed.…”
Section: Résumémentioning
confidence: 99%
“…14,40,43,45,46 Literature on long-term functional outcomes with RBCT in TBI patients is limited and fails to show any improvement following RBCT. [45][46][47] Both Hb and cerebral oxygenation-based targets have been used and studied to decide RBCT in these patients. In studies targeting physiologic parameters, RBCT has shown differential improvement in TBI patients.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…However, the potential benefits of RBCT to avoid anemia and reduce cerebral tissue hypoxia may be opposed by the potentially adverse effects related to this therapy [ 25 ▪ ]. Several studies have shown that RBCT administration in TBI is associated with increased mortality [ 11 , 14 , 34 , 41 , 42 , 43 ▪▪ , 44 ], decreased functional outcomes [ 39 , 42 , 45 ▪ , 46 ], increased ICU length of stay [ 47 ], and impaired cerebral autoregulation [ 48 ]. Furthermore, compared to a restrictive strategy, a liberal transfusion strategy applying a threshold trigger of 10 g/dl was associated with an increased risk of progressive cerebral hemorrhagic injury [ 49 ▪ ] and thromboembolic events [ 10 ].…”
Section: Effects Of Anemia and Red Blood Cell Transfusions On Traumatmentioning
confidence: 99%